(3agQSJ cJH GHf YQHis - (3eMeO Hf Ydj Hf eMeO Hf YQHj , CHh HcQ GdMGJej GdWGFj GdCfOdSj, GdeYQha HeMjj GdOjf GHf YQHj,J (B638 (3g` s ((3EHQGgje Hf eMeO Hf eXgQ GdTjNi s)
(3ChdgG (B:s
(3bGd GdTjN Hf GdYQHi GdWGdHi GdMGJei GdCfOdSi CeG HYO aEfg SCdfi HYV GdENhGf Cf CbjO dg ai gPg GdChQb LejY eG UfaJg hCfTCJg ai WQjb GdMbGFb s
(3BNQgG (B:s
(3hGdfhe hGdjbXI hGdYHO hGdQH JeJ HYhf Gddg JYGdi hMSf Jhajbg s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B281 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B114s
(3JHUQGJ GdCUd (B:s
Keywords: (3agGQS hecJHGJs